Molecular Characteristics of Batanghari, Tambago, Orange, and Mandiangin Giant Gourami Strains - Nuryanto, Agus; Pulungsari, Anatasia Endang (Biosaintifika: Journal of Biology & Biology Education, 2017)
Morphological variations among geographic and can be identified as different species. However, a lot of studies proved that morphological variations are also common in conspecific individuals. Therefore, precise identification using additional characters is vital, such as using a molecular marker. Here, we characterized Batanghari, Tambago, Orange, and Mandiangin gourami strains using the cytochrome b gene to evaluate their taxonomic status. Partial sequences of cytochrome b gene were sequenced for 40 individuals. Taxonomic status was checked for giant gourami sequences available in GenBank. Kimura 2-Parameter genetic distances were calculated in MEGA6 software. Haplotype and nucleotide diversity within population and ?st-value among populations were estimated in Arlequin software. Phylogenetic relationship was reconstructed using the neighbor-joining method in MEGA6 software based on Kimura 2-parameter model with 1000 pseudobootstraps. Taxonomic identification results in 99% sequences homology to Osphronemus goramy sequences (accession number KU984978.1 and AY763768.1), means that all strains belong to single species. Low genetic distances, medium haplotype and low-level nucleotide diversity were observed among strains. Pairwise ?st-comparison indicates no genetic differences among Sumatera strain, whereas strong genetic structures observed between Sumatera and Mandiangin strains. The phylogenetic tree showed that Mandiangin formed separate subclades from other strains with bootstraps value of 100%. This finding has important implication for breeding sciences and efforts.